The Efficacy of Murabahah Agreements in Personal Financing Schemes: A Case Study of KSPPS BMT NU in Rural Indonesia - Shinta Amelia Putri; Nita Aprilia; Intan Yulianti; Muhammad Fauzinudin Faiz (LP2M IAIN Palopo, 2025)
This study aims to analyze the effectiveness of murabahah agreements in personal financing schemes at KSPPS BMT NU, especially at the Wringin Bondowoso branch, Indonesia. This research uses a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews with semi-structured interviews and using purposive techniques in determining respondents, direct observation, and documentation related to the procedures and implementation of the murabahah agreements. The results showed that KSPPS BMT NU Wringin Branch has successfully implemented the murabahah agreements in accordance with sharia principles. The transparent financing process and clear profit margin are the main factors in increasing customer trust. In addition, this murabaha contract contributes to increasing access to financing for the Wringin village community. The results of this study provide important insights into the application of murabahah agreements in Islamic microfinance institutions and their impact on the economic development of the ummah. This study recommends the need for further development in Islamic financing practices as well as suggestions for future research that can explore other aspects of the murabahah contract and its impact on community welfare